115k views
0 votes
Solve for t. √52−t=72

A. t = 2√13 + 72
B. t = 2√13 - 72
C. t = -2√13 - 72

User Ea
by
5.1k points

2 Answers

2 votes
That's it so i don't think your answer was on there
Solve for t. √52−t=72 A. t = 2√13 + 72 B. t = 2√13 - 72 C. t = -2√13 - 72-example-1
User Loc Tran
by
5.2k points
3 votes

Answer:

The correct answer is option A.

Explanation:

Given =
√(52)-t=72

To find = t = ?

Solution


√(52)-t=72


√(2* 2* 3)-t=72

Identity =
√(x* x)=x


2√(3)-t=72


2√(3)+7=t

The value of the t is the option A.

User Osayilgan
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.